Therapeutic role of resveratrol against hepatocellular carcinoma: A review on its molecular mechanisms of action - Sanchari Bhattacharya; Angela Perris; Junaid Jibran Jawed; Muddasarul Hoda (Elsevier, 2023)
Introduction: Resveratrol is an important phenolic phytochemical isolated from grapes and peanuts. Consumption of grapes and peanuts in the form of wines and delicacies has been a traditional practice since ancient times because of its flavor and therapeutic potential against wide range of diseases. The current review article aims to summarize various metabolic and cell signaling pathways that are modulated by resveratrol in order to inhibit development and progression of hepatocellular carcinoma. Methodology: An extensive literature survey of major scientific journals databases including ScienceDirect and Medline was undertaken using keywords "hepatocellular carcinoma, resveratrol". A detailed analysis of relevant research articles has led to delineation of various mechanisms of action of resveratrol against hepatocellular carcinoma models. Results: Literature search resulted in screening of 144 research publications, of which 103 research publications were published in last 10 years. However, in the last decade, no review article has been published summarizes various mechanisms of action of resveratrol against hepatocellular carcinoma. Our detailed analysis of relevant research publications led to summarization of reports of various mechanism of actions of resveratrol against hepatocellular carcinoma. Discussion/conclusion: Resveratrol has the potential to protect the liver against development of early-stage hepatocellular carcinoma. It also triggers apoptosis of abnormally proliferating hepatocytes. Metastasis and angiogenesis that are hallmarks of advanced cancer stage, are also significantly attenuated by resveratrol. Additionally, resveratrol, in combination with standard drugs and nutraceuticals may significantly enhance their therapeutic efficacy via chemosensitization and synergistic mechanisms, respectively.